Answer:
y = 2
Step-by-step explanation:
6y - 2(y + 1) = 3(y - 2) + 6
6y - 2y - 2 = 3y - 6 + 6
6y - 2y - 2 = 3y
4y - 2 = 3y
4y - 2 + 2 = 3y + 2
4y = 3y + 2
4y - 3y = 3y - 3y + 2
y = 2
Answer:
A. 6 dollars per week.
Step-by-step explanation:
Because if you look carefully in the graph, you would see that the dot on 1 week is above 5 dollars so therefore, it would be 6 dollars. To check, look at the next dot and see. You will see that the dot above 2 weeks is in the middle of 10 and 15 dollars.
Hope I helped.
Beck add like terms so you get
4x^2 -4x-15
lucy factor our negative so you left with -4x^2 +5x -10 +8x^2 -9x -5
simplify 4x^2 -4x -15
therefore both students answers simplify to 4x^2 -4x -15
Answer:
(x + 3)(2x + 5)
Step-by-step explanation:
Given
2x² + 6x + 5x + 15 ← grouping the terms
= (2x² + 6x) + (5x + 15) ← factor each group
= 2x(x + 3) + 5(x + 3) ← factor out (x + 3) from each term
= (x + 3)(2x + 5) ← in factored form
It’s being divided by -3, so that means the next number is 1/3, or one third